2018
DOI: 10.1002/ptr.6099
|View full text |Cite
|
Sign up to set email alerts
|

The safety of St John's wort (Hypericum perforatum) in pregnancy and lactation: A systematic review of rodent studies

Abstract: Herbal products are popular among women during the perinatal period. St John's wort (SJW), Hypericum perforatum, is a common remedy for mild depression, a problem prevalent in this population. Although the safety of herbal products must be investigated, ethical issues constrain intervention studies in humans. Hence, animal studies often inform clinical decisions. The objective of this study is to systematically review rodent studies assessing the safety of SJW during the perinatal period. A literature search t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In our previous study on whole extracts, St. John’s wort showed no significant effects up to a concentration of 30 μg/ml extract for all types of in vitro experiments, namely cell viability, apoptosis, genotoxicity, metabolic activity, and inhibition/induction of placental cell differentiation ( Spiess et al, 2021 ). In general, there is a lack of adequate clinical studies on the genotoxicity of St. John’s wort, as well as tests on reproductive toxicity, and fertility ( Greeson et al, 2001 ; Avila et al, 2018 ). Well known issues such as phototoxicity ( Onoue et al, 2011 ) and interactions with other medications ( Nicolussi et al, 2020 ) must be taken care of also during administration in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study on whole extracts, St. John’s wort showed no significant effects up to a concentration of 30 μg/ml extract for all types of in vitro experiments, namely cell viability, apoptosis, genotoxicity, metabolic activity, and inhibition/induction of placental cell differentiation ( Spiess et al, 2021 ). In general, there is a lack of adequate clinical studies on the genotoxicity of St. John’s wort, as well as tests on reproductive toxicity, and fertility ( Greeson et al, 2001 ; Avila et al, 2018 ). Well known issues such as phototoxicity ( Onoue et al, 2011 ) and interactions with other medications ( Nicolussi et al, 2020 ) must be taken care of also during administration in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Acanthopanax, commonly known as ciwujia or Siberian ginseng, is a traditional Chinese medicine that ameliorates cognitive dysfunction induced by cholinergic blockade (Li et al, 2016). Hypericum perforatum, also called St. John's wort, has been used as an antidepressant agent and a cognitive enhancer in rodents (Avila et al, 2018). Hypericum perforatum has been shown to induce positive effects on both mood and short-term verbal memory (Yechiam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 ] Hypericum perforatum L, also known as St. John wort, has been clinically used to treat depression symptoms and improve cognitive function. [ 45 ] Studies suggested the positive effects on mood and short-term verbal memory after using Hypericum perforatum L. [ 46 ] Consequently, SGJYC naturally deserves to have anti-depressive effects. It noted that SGJYC has been confirmed to have similar effects but fewer adverse reactions than escitalopram in alleviating depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%